Analysis of methotrexate and folate transport by multidrug resistance protein 4 (ABCC4): MRP4 is a component of the methotrexate efflux system - CHEN, Zhe-Sheng; LEE, Kun; WALTHER, Susan; RAFTOGIANIS, Rebecca Blanchard; KUWANO, Michihiko; HAO ZENG; KRUH, Gary D (Cancer research (Chicago, Ill.), 2002)
Human MRP4 (ABCC4, MOAT-B) is a lipophilic anion transporter that is able to confer resistance to nucleotide analogues and methotrexate (MTX). We previously investigated the implications of the ability of MRP4 to confer resistance to nucleotide analogues and determined that the pump is competent in the MgATP-energized transport of cyclic nucleotides and estradiol 17beta-D-glucuronide. Here we examine the potential role of MRP4 in conferring resistance to MTX and related processes by determining the selectivity of the transporter for MTX, MTX polyglutamates, and physiological folates. In so doing, it is shown that MRP4 is active in the transport of MTX as well as the physiological folates folic acid (FA) and N(5)-formyltetrahydrofolic acid (leucovorin). MTX, FA, and leucovorin are subject to high capacity [V(max(MTX)), 0.24 +/- 0.05 nmol/mg/min; V(max (FA)), 0.68 +/- 0.14 nmol/mg/min; V(max(leucovorin)), 1.95 +/- 0.18 nmol/mg/min], low affinity [K(m(MTX)), 0.22 +/- 0.01 mM; K(m(FA)), 0.17 +/- 0.02 mM; K(m (leucovorin)), 0.64 +/- 0.23 mM] transport by MRP4. In addition, as would be expected were MRP4 a component of the MTX efflux system, its capacity to transport this agent is abrogated by the addition of a single glutamyl residue. It is also shown that glutamylation similarly affects the ability of MRP2 to transport MTX. On the basis of these transport properties, it is concluded that the efflux system for MTX includes MRP2 and MRP4, in addition to MRP1 and MRP3, and that MRP4 represents a common efflux system for both MTX and certain nucleotide analogues.